Analisis Pengaruh Temperatur dan Kelembaban Ruang Kelas terhadap Kelelahan pada Mahasiswa - Erlina Nurochman; Retno Widiastuti (Universitas Sarjanawiyata Tamansiswa, 2022)
Many schools and campuses in Indonesia are built without considering the predetermined room temperature standards, so they are far from comfortable. Based on SNI 03-6572-2001, the optimal comfort category in Indonesia is 22.8Â°C-25.8Â°C. This study aims to determine the effect of temperature and humidity in the classroom on student fatigue and performance. The research was conducted using observation methods, questionnaires, and literature studies. The research was conducted at the UST Integrated Laboratory with 30 students as respondents living in the Special Region of Yogyakarta. The sample of students working on academic potential test questions by setting a specific temperature level, then filling out a subjective fatigue questionnaire. Data processing is done by correlation analysis and regression analysis. The results showed that the variables of temperature and humidity had a negative correlation with the fatigue variable with a deficient category and simultaneously had no significant effect. In comparison, the temperature and humidity variables do not correlate to the performance variables and simultaneously have no significant effect.